On the Importance of UX Quality Aspects for Different Product Categories - Schrepp, Martin; Kollmorgen, Jessica; Meiners, Anna-Lena; Hinderks, Andreas; Winter, Dominique; Santoso, Harry B.; Thomaschewski, Jörg (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2023)
User experience (UX) is a holistic concept. We conceptualize UX as a set of semantically distinct quality aspects. These quality aspects relate subjectively perceived properties of the user interaction with a product to the psychological needs of users. Not all possible UX quality aspects are equally important for all products. The main use case of a product can determine the relative importance of UX aspects for the overall impression of the UX. In this paper, the authors present several studies that investigate this dependency between the product category and the importance of several well-known UX aspects. A method to measure the importance of such UX aspects is presented. In addition, the authors show that the observed importance ratings are stable, i.e., reproducible, and hardly influenced by demographic factors or cultural background. Thus, the ratings reported in our studies can be reused by UX professionals to find out which aspects of UX they should concentrate on in product design and evaluation.
Keywords: questionnaire; UX; IJIMAI